CONCEPTUAL ANALYSIS OF MODERN EUROSCEPTICISM - Milena Apostolovska Stepanoska; Hristina Runcheva Tasev (Institute Of Economic Development And Social Researches Publications, 2024)
Understanding euroscepticism goes beyond normative concerns about deepening European integration. It encompasses various aspects of political behavior, identities, public policies, democratic legitimacy, economy, ideology, and more. Euroscepticism is a complex and evolving phenomenon that lacks a universally accepted theoretical framework. Broadly, it denotes opposition to the European Union, whether in its entirety as a supranational entity or in its current structure, form, and political trajectory. Furthermore, euroscepticism manifests across the political spectrum, from left to right. Factors such as economic crises, fiscal policies, and the refugee crisis have intensified negative sentiments toward the EU among its populace. This environment has fostered the growth of eurosceptic parties and groups espousing populist and nationalist agendas. This study aims to delineate the contemporary dimensions of euroscepticism within the EU, following a review of the theoretical framework and essential conceptual clarifications related to euroscepticism. The results indicate that euroscepticism primarily revolves around concerns regarding sovereignty, identity, and the level of trust in national political systems. Additionally, euroscepticism correlates with the two significant crises that have challenged the EU and considerably tarnished its reputation: the economic crisis and the refugee crisis.
Keywords: Euroscepticism, Populism, Ideology, European Union